La población por «testigo». Comportamientos demográficos y cambios sociales en España desde mediados de los años 70 - Arón Cohen (Cahiers de Civilisation Espagnole Contemporaine)
The study of demographic facts provides important support for general social analysis. Their signs are wake-up calls and invite us to think of them as consequences and as factors. Over the past four or five decades, Spanish demography has experienced deep and accelerated changes, which cannot leave indifferent those who, from varied academic fields, follow the recent trends of Spanish society, without applying a skilled demographic analysis. Two parallel examples of these manifestations (fertility of unmarried women and immigration) give rise to a reflection on the interaction between demographic behaviors, political-institutional changes and social (socio-economic and socio-cultural) dynamics. Frequent, hasty or simply spurious causalities (either spontaneous or promoted), are part of the analysis and should not be confused with it.